The Retrial Model in Spain - Lara-López, Antonio María (Springer Nature, 2023)
The second instance in criminal proceedings has been (and continues to be) a major problem in the Spanish procedural system. After innumerable criticisms from international courts and organizations, Spain recognized the need to establish an appeal that would open the second instance in the criminal justice system and that would allow, from a broad point of view, the review of the conviction by the convicted person. After several unsuccessful attempts, the establishment of the second instance was set forth in 2015. However, instead of following the classic doctrine which recommended that this appeal should be of an ordinary nature, the aforementioned law introduces a restricted appeal of an extraordinary nature. Faced with this situation, the current Draft Bill for a new Criminal Procedure Act does not improve the situation. The reason for this decision is the principle of immediacy and its understanding by the ECtHR, and the SCC, essentially stated that a person acquitted in the first instance could not be sentenced in the second instance without having been heard first. This doctrine has weighed on the 2015 reform and continues to do it in relation to the aforementioned Draft Bill since. The aim of this chapter is to analyse the influence of the doctrine emanating from the ECtHR in relation to the above issue and its reception by Spanish legislation and its courts of justice, mainly from the correct understanding of what should constitute a true second instance in relation to the principle of immediacy.
https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Apelación - España; Derecho procesal; Derecho procesal penal; Recurso de apelación penal; Segunda instancia; Derechos fundamentales